RADIO HAMZANWADI SEBAGAI MEDIA ISLAMI - KURNIAWAN, ANDRI (TASAMUH, 2020)
Radio Dakwah Hamzanwadi (RHN) in the vortex 4.0era is still a mass communication media that channels ideas and information in the form of sound in a public and open manner, in the form of regular and continuous programs. RHN as the main optional community in absorbing the information and religious knowledge. This study uses a qualitative method of phenomenological type by collecting observation and documentation data. The substance of this research focuses on RHN programs and content as broadcasting media in NTB. RHN can be polarized as an Islamic media by paying attention to the substance and broadcast programs that are carried out continuously, such as Islamic programs through regular morning recitations at the Al-Abrar Mosque, Khiwar Mustasyar programs, reading the Hizib Nahdlatul Wathan, and also the general recitation of Tuan Guru Bajang (TGB) Dr. KH. Muhammad Zainul Majdi, M.A becomes the main broadcast after each subuh and magrib prayer.